Influence of anti-Spike protein antibody levels on tocilizumab efficacy in hospitalized patients with severe COVID-19 pneumonia: a post-hoc analysis of the COVACTA trial - José Aguareles; Carles Forné; Ana García-Casas; Guillermo Santamaría-Corral; Daniel Carnevali-Ruiz; Gabriel Sotres-Fernández; Javier T Solera; Pablo Guisado-Vasco (BMC Infectious Diseases)
Abstract Background Our aim in this work is to find biomarkers to optimize therapy with IL-6 inhibitors, as not all clinical trials have shown clear benefits on mortality or mechanical ventilation progression. Given the link between delayed seroconversion and higher complication risks, we aim to test if evaluating SARS-CoV-2 spike protein antibody status before treatment could enhance IL-6 inhibitor therapy effectiveness in COVID-19 patients. Methods We conducted a post hoc analysis of the COVACTA study, a phase 3, randomized, double-blind, placebo-controlled trial of the efficacy and safety of tocilizumab in hospitalized patients with severe COVID-19. Cox and logistic regression analysis were used to assess the tocilizumab’s efficacy in severe COVID-19 patients on survival and ICU stay at day 28, based on SARS-CoV-2 S-spike and neutralizing antibody levels. Results Tocilizumab reduced 28-day mortality over placebo in patients with low S-spike antibody titers (20% vs. 29%). No benefit was observed for higher antibody levels. Patients with low S-spike antibody levels treated with tocilizumab exhibited a lower probability of ICU stay at day 28 compared to those treated with placebo (63% vs. 82%). No significant differences were noted in mortality and ICU stay based on whole neutralizing antibody titers. Conclusions Our findings suggest that using IL-6 inhibitors in severe COVID-19 patients with low S-spike antibody titers may improve clinical outcomes. Clinical trial Not applicable.